Fisheries - Thayaparan, K.; International Centre for Ethnic Studies; Project on Institution Building: Administrative Arrangements for Implementing Devolution (Colombo : International Centre for Ethnic Studies, 2001)
With reference to the government policy of Sri Lanka.
"Project on Institution Building: Administrative Arrangements for Implementing Devolution."
Microfiche.
Keywords: Fisheries -- Sri Lanka; Fishery policy -- Sri Lanka